2003
DOI: 10.1016/s0014-5793(03)01408-x
|View full text |Cite
|
Sign up to set email alerts
|

High and low affinity receptors mediate growth effects of gastrin and gastrin‐Gly on DLD‐1 human colonic carcinoma cells

Abstract: Gastrin (G17) and N-carboxymethylgastrin (G17-Gly) have been shown to stimulate the growth of colon cancer cells both in vivo and in vitro. The identity of the receptor mediating these e¡ects is controversial. A recent study demonstrated the presence of a low a⁄nity binding site for G17 and G17-Gly on the DLD-1 human colon cancer cell line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 39 publications
1
12
0
1
Order By: Relevance
“…In recent papers, Ahmed et al reported the importance of N and C terminal sequences in the gastrin-Gly molecule for conferring high and low affinity binding to novel receptors on colon cancer cells, respectively; these binding sites were distinct from CCK 1 R and CCK 2 R (55;56). Both the low and high affinity binding sites mediated the growth effects of gastrin-like molecules on colon cancer cells (56), suggesting that different receptor sub-types, other than CCK 1 R and CCK 2 R, may be involved in mediating growth factor effects of gastrins/progastrins. Based on our studies (6), it is possible, that the high affinity binding receptor proteins identified by Ahmed et al (6;55;56) may be ANX II.…”
Section: A Annexin-ii Is a High Affinity Receptor (Binding) Proteinmentioning
confidence: 99%
“…In recent papers, Ahmed et al reported the importance of N and C terminal sequences in the gastrin-Gly molecule for conferring high and low affinity binding to novel receptors on colon cancer cells, respectively; these binding sites were distinct from CCK 1 R and CCK 2 R (55;56). Both the low and high affinity binding sites mediated the growth effects of gastrin-like molecules on colon cancer cells (56), suggesting that different receptor sub-types, other than CCK 1 R and CCK 2 R, may be involved in mediating growth factor effects of gastrins/progastrins. Based on our studies (6), it is possible, that the high affinity binding receptor proteins identified by Ahmed et al (6;55;56) may be ANX II.…”
Section: A Annexin-ii Is a High Affinity Receptor (Binding) Proteinmentioning
confidence: 99%
“…However, in the periphery where receptors are exposed to both circulating hormones, the main endogenous ligand is likely to be gastrin since its concentrations in plasma are about five to ten times higher than those of CCK. Neither progastrin nor the Gly-gastrins are considered to be endogenous ligands of the CCK-2 receptor, but both are reported to have their own characteristic pattern of biological activities, and these are thought to be mediated by non-CCK-1/non-CCK-2 receptors [1,112]. The term ''CCK-C receptor'' is sometimes used to describe non-CCK-1/non-CCK-2 receptors responding to progastrin-derived peptides.…”
Section: Cck-2 Receptors and Signal Transductionmentioning
confidence: 99%
“…Furthermore, the biological effects of progastrin and gly-gastrin are not blocked by CCK-B receptor antagonists (Seva et al, 1994;Stepan et al, 1999;Baldwin et al, 2001), and amidated gastrin and gly-gastrin stimulate different downstream signalling events (Todisco et al, 2001). Potential alternative receptors for progastrin and gly-gastrin have been suggested (Seva et al, 1994;Baldwin, 1995a;Singh et al, 1995;Smith et al, 2002;Ahmed et al, 2004).…”
mentioning
confidence: 99%